A opção cooperativa: os trabalhadores diante da falta de alternativas de ocupação e renda - Mondadore, Ana Paula Carletto (Universidade Federal de São Carlos, 2007)
From the 90 s decade, the economical, technological and organizational changes that characterized the process of productive restructuralization in Brazil had as a result deep transformations on the job market. In this context the work and production cooperatives resurge, perceived as a possible alternative of occupation for the workers. These cooperatives have caused an ample debate about their effective role and possibilities. On one hand, there are the defenders of the called Solidarity Economy, who see the cooperatives organization not only as an option of unemployment, but a chance, for the workers to perform a change inside the structures of capitalism. On the other hand, the cooperatives are perceived according to their functionality for the capital, being organized to attend the necessities of cost reduction at the companies through the elimination of the social benefits included in the wage relation. We investigated a cooperative that produces clothes, which works outsourced for a big company of the sector, to recover the workers perception about the self-managing work. We noticed that the option for the co-operative work reveals a lot of dimensions, from the economical choice, through the guarantee of job and high salaries to the characteristical autonomy of the self-managing enterprises, but the deep transformation in the relation between capital and work is far from effectively happen in the day-by-day totality of the cooperative work, mainly if we think about the relation between company and cooperative
Keywords: Sociologia do trabalho; Cooperativa de trabalho; Cooperativa de produção; Autogestão no trabalho; Terceirização; Work cooperatives; Production cooperatives; Self-management; Outsourcing; CIENCIAS HUMANAS